Who can benefit from augmented reality in chemistry? Sex differences in solving stereochemistry problems using augmented reality - Habig, Sebastian (British journal of educational technology, 2020)
This paper is about augmented reality (AR) and its potentials to support students in handling scientific representations. For this purpose, first representations are examined from a science educational and instructional psychology perspective. After giving a short overview of AR in general and how it can be delineated from virtual reality (VR), potential advantages of an educational use of AR are outlined considering typical difficulties of students when learning with scientific representations. Since literature frequently reports sex differences in spatial abilities, this study focuses on potential differential effects in the use of AR depending on sex. Against this background, AR might be a tool which can help to compensate for disadvantages in spatial abilities. In order to investigate this question, chemistry students had to answer 20 items related to stereochemistry, a concept that places high demands on mental spatial rotation skills. While one half of the items had to be solved using two-dimensional (2D) ball-and-stick figures of molecules, the other half had to be answered with the help of AR representations. Due to the aforementioned sex differences regarding visuo-spatial abilities between males and females found in the literature, it is hypothesized that AR representations will support all students but females in particular by reducing cognitive load. If this assumption is correct, the AR items would have to be correctly solved by the students more often than the 2D items. The results of analyses of variance indeed reveal a significant effect of the sex variable dependent on the type of representation. In addition, a questionnaire was administered to survey the students’ attitudes towards learning with the AR app used.
Created from Fastlane, Scopus look-up